Precepting nurse practitioner students in the graduate nurse education demonstration: A cross-sectional analysis of the preceptor experience. Issue 11 (November 2019) - Todd, Barbara A.; Brom, Heather; Blunt, Elizabeth; Dillon, Patricia; Doherty, Caroline; Drayton-Brooks, Shirlee; Hung, Irene; Montgomery, Kymberlee; Peoples, Lynda; Powell, Mary; Vanacore, Denise; Whalen, Dara; et al.
ABSTRACT: Background: The Graduate Nurse Education (GNE) Demonstration seeks to increase the number of advanced practice registered nurses (APRNs) in clinical practice. With the overall increase in APRN programs and, particularly, enrollment in nurse practitioner (NP) programs, there is growing competition among students to secure quality clinical precepting experiences. Purpose: This study describes NPs' and physicians' experiences with precepting APRN students within the Greater Philadelphia GNE Consortium. Methods: This was a cross-sectional descriptive survey of 1, 021 NP and physician preceptors who provided clinical practicum experiences for at least one of the nine Greater Philadelphia GNE Consortium schools. Results: Differences between NP and physician precepting experiences regarding the importance of various factors in their decisions to precept were explored. Both NP and physician preceptors provide clinical practicum experiences to APRN students because they enjoy doing so. However, they differ regarding what they find important in their decisions to precept such as having protected time to precept and educational opportunities. Implications for practice: As universities work to recruit quality preceptors, they should consider tailoring their approach based on the preceptor's clinical role. In addition, schools located within the same region should consider streamlining administrative processes to form sustaining and productive clinical partnerships.